A composite diaphragm for alkaline water electrolysis and a preparation method thereof
By hydrophilic modification of the polyphenylene sulfide mesh and coating with polysulfone resin, nanozirconium dioxide and calcium oxide, a composite membrane is formed, which solves the problems of insufficient alkali corrosion resistance and airtightness of the existing membrane, and achieves further development High hydrophilicity and alkali resistance, extend service life and improve the safety of the electrolysis process and hydrogen production purity.
Patent Information
- Application Number
- CN202311850378.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-12-29
AI Technical Summary
In the existing alkaline electrolytic hydrogen production technology, the alkali corrosion resistance and airtightness of the separator are insufficient, which affects electrolytic energy consumption, hydrogen production purity and safety.
The polyphenylene sulfide mesh is hydrophilicly modified and the surface is coated with polysulfone resin, nanozirconium dioxide and calcium oxide to form a composite separator. This method improves the hydrophilicity and alkali corrosion resistance of the membrane, and enhances the bonding strength between the barrier layer and the polyphenylene sulfide mesh.
It significantly improves the hydrophilic properties and alkali corrosion resistance of the composite separator, extends its service life, and improves the safety of the electrolysis process and hydrogen production purity.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alkaline water electrolysis hydrogen production, and in particular to an alkaline water electrolysis composite diaphragm and a preparation method thereof. Background Art
[0002] The main method for industrial large-scale production of hydrogen is water electrolysis. At present, this process is relatively mature, not only with high yield, but also more environmentally friendly. Among them, water electrolysis is mainly divided into alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEM), solid oxide water electrolysis (SOEC) and anion exchange membrane water electrolysis (AEM), among which alkaline water electrolysis technology is the most mature.
[0003] The diaphragm is a key material for alkaline water electrolysis hydrogen production technology. Its performance determines the electrolysis energy consumption, hydrogen production purity and safety of the electrolyzer under the same catalytic electrode conditions. In general, an alkaline aqueous solution with a mass concentration of 25-30% as an electrolyte for electrolytic hydrogen production will have a strong corrosive effect on the diaphragm. Therefore, the diaphragm should have good alkali corrosion resistance. In addition, in order to prevent the mixing of hydrogen and oxygen produced during the electrolysis process from affecting the purity of the product and the safety of the electrolyzer, the diaphragm should also have good air tightness. The composite diaphragm has the advantages of both organic diaphragms and inorganic diaphragms, and includes three parts: organic polymer substances, inorganic nanoparticles and support nets. Although the current research on composite porous diaphragms has achieved certain results, improving the bonding performance between inorganic nanoparticles and diaphragms and improving the hydrophilicity of diaphragms are still the pursuit of this technical field. Summary of the invention
[0004] The object of the present invention is to provide an alkaline water electrolysis composite diaphragm and a preparation method thereof to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an alkaline water electrolysis composite diaphragm and a preparation method thereof, comprising the following steps:
[0006] Step 1:
[0007] Weigh dopamine hydrochloride, add it to the tris(hydroxymethyl)aminomethane) solution to obtain a dopamine hydrochloride solution; wash the polyphenylene sulfide net alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 8.5-9, heat to 60-70°C to react for 20-24h, take out the polyphenylene sulfide net, and obtain a polydopamine-modified polyphenylene sulfide net;
[0008] Step 2:
[0009] S21: 3-hydroxy-2-methylpropylene, triphenylmethane triisocyanate, and catalyst dibutyltin dilaurate are dispersed in ethyl acetate, the temperature is raised to 70-80° C. under a nitrogen environment, the mixture is stirred for reaction for 8-10 hours, and the ethyl acetate is removed by reduced pressure distillation to obtain a double bond modified polyurethane prepolymer;
[0010] S22: Take toluene diisocyanate, polypropylene glycol 2000, catalyst dibutyltin dilaurate, dimethylolpropionic acid, 1,4-butanediol, raise the temperature to 80-90° C., react for 3-5 hours, and obtain a polyurethane prepolymer;
[0011] S23: adding the double bond modified polyurethane prepolymer to the polyurethane prepolymer to obtain a mixed polyurethane prepolymer;
[0012] S24: reacting the mixed polyurethane prepolymer and triethylamine at 50-60°C for 30-60 minutes; continuing to add ethylenediamine for 1-2 hours, and adding deionized water for emulsification for 1-2 hours to obtain a polyurethane coating with a solid content of 30-50%;
[0013] S25:
[0014] The polyurethane coating, 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid and a photoinitiator are mixed and stirred to obtain a binder;
[0015] Step 3:
[0016] Spraying the adhesive on both sides of the polydopamine-modified polyphenylene sulfide net, with a single-side spraying thickness of 50-200 μm, and curing with ultraviolet light to obtain a hydrophilic polyphenylene sulfide net;
[0017] Step 4:
[0018] The polysulfone resin, zirconium dioxide and calcium carbonate are mixed to obtain a polysulfone casting solution, the polysulfone casting solution is coated on the surface of the hydrophilic polyphenylene sulfide net, and a composite diaphragm is obtained after passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank.
[0019] Furthermore, in step 1, the mass concentration of the dopamine hydrochloride solution is 2-3%.
[0020] Furthermore, in S21, the molar ratio of 3-hydroxy-2-methylpropene to triphenylmethane triisocyanate is (1~2):1.
[0021] Furthermore, in S22, the amount of each component, by weight, is 75-82 parts of toluene diisocyanate, 95-103 parts of polypropylene glycol 2000, 0.1-0.3 parts of catalyst dibutyltin dilaurate, 16-18 parts of dihydroxymethylpropionic acid, and 5-8 parts of 1,4-butanediol.
[0022] Furthermore, in S23, the contents of the components in the mixed polyurethane prepolymer are, by weight percentage, 30-40% of the double bond modified polyurethane prepolymer and 60-70% of the polyurethane prepolymer.
[0023] Furthermore, in S24, the mass ratio of the mixed polyurethane prepolymer, triethylamine and ethylenediamine is (36-45):(5-6):(2-4).
[0024] Furthermore, in S25, the contents of the components in the binder are, by weight, 40 to 50 parts of polyurethane coating, 5 to 15 parts of 2-acrylamide-2-methylpropane sulfonic acid, 8 to 10 parts of acrylic acid, and 0.8 to 1 part of photoinitiator.
[0025] Furthermore, in step 4, the contents of the components in the polysulfone casting solution are, by weight percentage, 10-15% polysulfone resin, 75-80% zirconium dioxide, and 5-10% calcium carbonate.
[0026] Furthermore, in step 4, the particle size of zirconium dioxide is 50-500 nm; the particle size of calcium carbonate is 50-500 nm.
[0027] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention firstly performs hydrophilic modification on the polyphenylene sulfide net, and then coats the polysulfone resin, nano zirconium dioxide and calcium oxide on the hydrophilic modified polyphenylene sulfide net to obtain an alkaline electrolytic hydrogen production diaphragm. The polyphenylene sulfide net is first modified with polydopamine to improve its hydrophilicity. Due to the unique surface viscosity of polydopamine, the adhesion performance of the surface of the modified polyphenylene sulfide net is greatly improved. The double-bond modified polyurethane prepolymer and the conventional polyurethane prepolymer are mixed, and a polyurethane containing a double bond in the side chain is obtained by chain extension, which is mixed with 2-acrylamide-2-methylpropane sulfonic acid and acrylic acid and coated on the polyphenylene sulfide net modified by polydopamine, and the sulfonic acid group and the carboxyl group are introduced by photocuring, thereby improving the hydrophilicity and alkali corrosion resistance of the polyphenylene sulfide net, enhancing the bonding strength between the barrier layer and the polyphenylene sulfide net, and extending the service life of the polyphenylene sulfide net.
[0028] It should be noted that when preparing the double-bond modified polyurethane prepolymer, the molar ratio of the reactants 3-hydroxy-2-methylpropene and triphenylmethane triisocyanate needs to be controlled at (1~2):1. If the 3-hydroxy-2-methylpropene is excessive, the triphenylmethane triisocyanate will fully react with the hydroxyl group, and the double bond cannot be introduced into the molecular chain of the polyurethane, and the final modification effect of the polyurethane on the polyphenylene sulfide network is reduced. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Materials used in the present invention and their sources: polyphenylene sulfide net comes from Tianjin Key Laboratory of Pulp and Papermaking, with a gram weight of 570±30 g / m; polypropylene glycol 2000 comes from Hai'an Petrochemical Plant; the photoinitiator is photoinitiator 1173, which comes from Shanghai Houcheng Fine Chemical Co., Ltd.; zirconium dioxide comes from Juguang Evonik, with an average particle size of 50~80 nm; calcium carbonate comes from Xianfeng Nano, 101099, with an average particle size of 50~100 nm; polysulfone resin comes from Shanghai Lanrun Chemical Co., Ltd.; item number 25135-51-7.
[0031] Example 1: An alkaline water electrolysis membrane and a preparation method thereof, comprising the following steps:
[0032] Step 1:
[0033] Weigh dopamine hydrochloride, add it to tris(hydroxymethylaminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide network alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 8.5, heat to 60°C to react for 20h, take out the polyphenylene sulfide network, and obtain a polydopamine-modified polyphenylene sulfide network;
[0034] Step 2:
[0035] S21: 1 mol of 3-hydroxy-2-methylpropylene and 1 mol of triphenylmethane triisocyanate were added with a catalyst of dibutyltin dilaurate (0.5% of the total mass of the reactants) and dispersed in ethyl acetate, the temperature was raised to 70° C. under a nitrogen environment, the mixture was stirred and reacted for 8 h, and the ethyl acetate was removed by reduced pressure distillation to obtain a double bond modified polyurethane prepolymer;
[0036] S22: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dimethylol propionic acid, and 5g 1,4-butanediol, raise the temperature to 80°C, and react for 3h to obtain a polyurethane prepolymer;
[0037] S23: adding 30% of the double bond modified polyurethane prepolymer to 70% of the polyurethane prepolymer by weight to obtain a mixed polyurethane prepolymer;
[0038] S24: At 50° C., 36 g of mixed polyurethane prepolymer and 5 g of triethylamine were reacted for 30 min; 4 g of ethylenediamine was added to react for 1 h, and deionized water was added to emulsify for 1 h to obtain a polyurethane coating with a solid content of 50%;
[0039] S25:
[0040] 50 g of polyurethane coating, 5 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of acrylic acid and 1 g of photoinitiator were mixed and stirred to obtain a binder;
[0041] Step 3:
[0042] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0043] Step 4:
[0044] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0045] Example 2: An alkaline water electrolysis membrane and a method for preparing the same, comprising the following steps:
[0046] Step 1:
[0047] Weigh dopamine hydrochloride, add it to tris(hydroxymethylaminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide network alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 8.8, heat to 65°C to react for 22h, take out the polyphenylene sulfide network, and obtain a polydopamine-modified polyphenylene sulfide network;
[0048] Step 2:
[0049] S21: 1 mol of 3-hydroxy-2-methylpropylene and 1 mol of triphenylmethane triisocyanate were added with a catalyst of dibutyltin dilaurate (0.5% of the total mass of the reactants) and dispersed in ethyl acetate, the temperature was raised to 75° C. under a nitrogen environment, the mixture was stirred and reacted for 9 h, and the ethyl acetate was removed by reduced pressure distillation to obtain a double bond modified polyurethane prepolymer;
[0050] S22: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dimethylol propionic acid, and 5g 1,4-butanediol, raise the temperature to 85°C, and react for 4h to obtain a polyurethane prepolymer;
[0051] S23: adding 30% of the double bond modified polyurethane prepolymer to 70% of the polyurethane prepolymer by weight to obtain a mixed polyurethane prepolymer;
[0052] S24: At 55° C., 36 g of mixed polyurethane prepolymer and 5 g of triethylamine were reacted for 45 min; 4 g of ethylenediamine was added to react for 1.5 h, and deionized water was added to emulsify for 1.5 h to obtain a polyurethane coating with a solid content of 50%;
[0053] S25:
[0054] 50 g of polyurethane coating, 5 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of acrylic acid and 1 g of photoinitiator were mixed and stirred to obtain a binder;
[0055] Step 3:
[0056] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0057] Step 4:
[0058] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0059] Example 3: An alkaline water electrolysis membrane and a method for preparing the same, comprising the following steps:
[0060] Step 1:
[0061] Weigh dopamine hydrochloride, add it to tris(hydroxymethylaminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide net alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 9, heat to 70°C to react for 24h, take out the polyphenylene sulfide net, and obtain a polydopamine-modified polyphenylene sulfide net;
[0062] Step 2:
[0063] S21: 1 mol of 3-hydroxy-2-methylpropylene and 1 mol of triphenylmethane triisocyanate were added with a catalyst of dibutyltin dilaurate (0.5% of the total mass of the reactants) and dispersed in ethyl acetate, the mixture was heated to 80° C. under a nitrogen atmosphere, stirred and reacted for 10 h, and the ethyl acetate was removed by vacuum distillation to obtain a double bond-modified polyurethane prepolymer;
[0064] S22: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dimethylol propionic acid, and 5g 1,4-butanediol, raise the temperature to 90°C, and react for 5h to obtain a polyurethane prepolymer;
[0065] S23: adding 30% of the double bond modified polyurethane prepolymer to 70% of the polyurethane prepolymer by weight to obtain a mixed polyurethane prepolymer;
[0066] S24: At 60° C., 36 g of mixed polyurethane prepolymer and 5 g of triethylamine were reacted for 60 min; 4 g of ethylenediamine was added to react for 2 h, and deionized water was added to emulsify for 2 h to obtain a polyurethane coating with a solid content of 50%;
[0067] S25:
[0068] 50 g of polyurethane coating, 5 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of acrylic acid and 1 g of photoinitiator were mixed and stirred to obtain a binder;
[0069] Step 3:
[0070] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0071] Step 4:
[0072] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0073] Example 4: An alkaline water electrolysis membrane and a method for preparing the same, comprising the following steps:
[0074] Step 1:
[0075] Weigh dopamine hydrochloride, add it to the tris(hydroxymethyl)aminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide net alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 9, heat to 60°C to react for 21h, take out the polyphenylene sulfide net, and obtain a polydopamine-modified polyphenylene sulfide net;
[0076] Step 2:
[0077] S21: 1 mol of 3-hydroxy-2-methylpropylene and 1 mol of triphenylmethane triisocyanate were added with a catalyst of dibutyltin dilaurate (0.5% of the total mass of the reactants) and dispersed in ethyl acetate, the temperature was raised to 75° C. under a nitrogen environment, the mixture was stirred and reacted for 9 h, and the ethyl acetate was removed by reduced pressure distillation to obtain a double bond modified polyurethane prepolymer;
[0078] S22: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dimethylol propionic acid, and 5g 1,4-butanediol, raise the temperature to 85°C, and react for 3h to obtain a polyurethane prepolymer;
[0079] S23: adding 30% of the double bond modified polyurethane prepolymer to 70% of the polyurethane prepolymer by weight to obtain a mixed polyurethane prepolymer;
[0080] S24: At 60° C., 36 g of mixed polyurethane prepolymer and 5 g of triethylamine were reacted for 30 min; 4 g of ethylenediamine was added to react for 1.5 h, and deionized water was added to emulsify for 1.5 h to obtain a polyurethane coating with a solid content of 50%;
[0081] S25:
[0082] 50 g of polyurethane coating, 7 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of acrylic acid and 1 g of photoinitiator were mixed and stirred to obtain a binder;
[0083] Step 3:
[0084] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0085] Step 4:
[0086] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0087] Example 5: An alkaline water electrolysis membrane and a method for preparing the same, comprising the following steps:
[0088] Step 1:
[0089] Weigh dopamine hydrochloride, add it to the tris(hydroxymethyl)aminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide net alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 9, heat to 65°C to react for 22h, take out the polyphenylene sulfide net, and obtain a polydopamine-modified polyphenylene sulfide net;
[0090] Step 2:
[0091] S21: 1 mol of 3-hydroxy-2-methylpropylene and 1 mol of triphenylmethane triisocyanate were added with a catalyst of dibutyltin dilaurate (0.5% of the total mass of the reactants) and dispersed in ethyl acetate, the temperature was raised to 75° C. under a nitrogen environment, the mixture was stirred and reacted for 9 h, and the ethyl acetate was removed by reduced pressure distillation to obtain a double bond modified polyurethane prepolymer;
[0092] S22: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dimethylol propionic acid, and 5g 1,4-butanediol, raise the temperature to 90°C, and react for 3h to obtain a polyurethane prepolymer;
[0093] S23: adding 30% of the double bond modified polyurethane prepolymer to 70% of the polyurethane prepolymer by weight to obtain a mixed polyurethane prepolymer;
[0094] S24: At 60° C., 36 g of mixed polyurethane prepolymer and 5 g of triethylamine were reacted for 60 min; 4 g of ethylenediamine was added to react for 1 h, and deionized water was added to emulsify for 2 h to obtain a polyurethane coating with a solid content of 50%;
[0095] S25:
[0096] 50 g of polyurethane coating, 12 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of acrylic acid and 1 g of photoinitiator were mixed and stirred to obtain a binder;
[0097] Step 3:
[0098] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0099] Step 4:
[0100] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0101] Example 6: An alkaline water electrolysis membrane and a method for preparing the same, comprising the following steps:
[0102] Step 1:
[0103] Weigh dopamine hydrochloride, add it to tris(hydroxymethylaminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide net alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 9, heat to 70°C to react for 24h, take out the polyphenylene sulfide net, and obtain a polydopamine-modified polyphenylene sulfide net;
[0104] Step 2:
[0105] S21: 1 mol of 3-hydroxy-2-methylpropylene and 1 mol of triphenylmethane triisocyanate were added with a catalyst of dibutyltin dilaurate (0.5% of the total mass of the reactants) and dispersed in ethyl acetate, the mixture was heated to 80° C. under a nitrogen atmosphere, stirred and reacted for 10 h, and the ethyl acetate was removed by vacuum distillation to obtain a double bond-modified polyurethane prepolymer;
[0106] S22: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dimethylol propionic acid, and 5g 1,4-butanediol, raise the temperature to 90°C, and react for 5h to obtain a polyurethane prepolymer;
[0107] S23: adding 30% of the double bond modified polyurethane prepolymer to 70% of the polyurethane prepolymer by weight to obtain a mixed polyurethane prepolymer;
[0108] S24: At 60° C., 36 g of mixed polyurethane prepolymer and 5 g of triethylamine were reacted for 60 min; 4 g of ethylenediamine was added to react for 2 h, and deionized water was added to emulsify for 2 h to obtain a polyurethane coating with a solid content of 50%;
[0109] S25:
[0110] 50 g of polyurethane coating, 15 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of acrylic acid and 1 g of photoinitiator were mixed and stirred to obtain a binder;
[0111] Step 3:
[0112] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0113] Step 4:
[0114] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0115] Comparative Example 1: The amount of 3-hydroxy-2-methylpropene in step 2 was increased, and the other parameters were the same as those in Example 1.
[0116] Step 1:
[0117] Weigh dopamine hydrochloride, add it to tris(hydroxymethylaminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide network alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 8.5, heat to 60°C to react for 20h, take out the polyphenylene sulfide network, and obtain a polydopamine-modified polyphenylene sulfide network;
[0118] Step 2:
[0119] S21: 3 mol of 3-hydroxy-2-methylpropylene and 1 mol of triphenylmethane triisocyanate were added with a catalyst of dibutyltin dilaurate (0.5% of the total mass of the reactants) and dispersed in ethyl acetate. The mixture was heated to 70° C. under a nitrogen atmosphere, stirred and reacted for 8 h, and the ethyl acetate was removed by vacuum distillation to obtain a double-bond modified polyurethane oligomer.
[0120] S22: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dimethylolpropionic acid, and 5g 1,4-butanediol, raise the temperature to 80°C, and react for 3h to obtain a polyurethane oligomer;
[0121] S23: adding 30% of double bond modified polyurethane oligomer to 70% of polyurethane prepolymer by weight to obtain a mixed polyurethane prepolymer;
[0122] S24: At 50° C., 36 g of mixed polyurethane prepolymer and 5 g of triethylamine were reacted for 30 min; 4 g of ethylenediamine was added to react for 1 h, and deionized water was added to emulsify for 1 h to obtain a polyurethane coating with a solid content of 50%;
[0123] S25:
[0124] 50 g of polyurethane coating, 5 g of 2-acrylamide-2-methylpropanesulfonic acid, 8 g of acrylic acid and 1 g of photoinitiator were mixed and stirred to obtain a binder;
[0125] Step 3:
[0126] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0127] Step 4:
[0128] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0129] Comparative Example 2: Conventional polyurethane coating was used as the binder, and the other parameters were the same as those in Example 2.
[0130] Step 1:
[0131] Weigh dopamine hydrochloride, add it to tris(hydroxymethylaminomethane) solution to obtain a 3% dopamine hydrochloride solution; wash the polyphenylene sulfide network alternately with ethanol and deionized water, add it to the dopamine hydrochloride solution after drying, add sodium hydroxide to adjust the pH value to 8.8, heat to 65°C to react for 22h, take out the polyphenylene sulfide network, and obtain a polydopamine-modified polyphenylene sulfide network;
[0132] Step 2:
[0133] S21: Take 75g toluene diisocyanate, 95g polypropylene glycol 2000, 0.3g catalyst dibutyltin dilaurate, 18g dihydroxymethylpropionic acid, and 5g 1,4-butanediol, raise the temperature to 85°C, and react for 4h to obtain a polyurethane prepolymer;
[0134] S22: At 55°C, 36g of polyurethane prepolymer and 5g of triethylamine were reacted for 45min; 4g of ethylenediamine was added to react for 1.5h, and deionized water was added to emulsify for 1.5h to obtain a polyurethane coating with a solid content of 50%;
[0135] Step 3:
[0136] The adhesive was sprayed on both sides of the polydopamine-modified polyphenylene sulfide mesh, with a single-side spraying thickness of 200 μm, and then cured by 250W, 365nm ultraviolet light to obtain a hydrophilic polyphenylene sulfide mesh;
[0137] Step 4:
[0138] By weight percentage, 15% polysulfone resin, 75% zirconium dioxide and 10% calcium carbonate are mixed to obtain a polysulfone casting solution, and the polysulfone casting solution is coated on the surface of a hydrophilic polyphenylene sulfide mesh with a coating thickness of 500 μm. After passing through an air bath, a gel bath, an annealing tank, a pickling tank and a cleaning tank, a composite diaphragm is obtained.
[0139] Experiment: The composite membranes in Examples 1 to 6 and Comparative Examples 1 to 2 were tested, and the results are shown in the following table.
[0140] Hydrophilicity test: characterize by the contact angle between the membrane surface and the alkali solution;
[0141] Alkali resistance test: The tensile strength of the composite diaphragm was tested using the method of GB / T3923.1-2013 and recorded as F1. The composite diaphragm was then placed in a 30wt% NaOH solution and heated to 90°C for 300h. The tensile strength was recorded as F2 again, and the breaking strength loss rate was calculated: loss rate = (F1-F2) / F1×100%.
[0142]
[0143] Conclusion: The composite membrane prepared by the present invention has good hydrophilic properties, and the alkali resistance of the polyphenylene sulfide network after hydrophilic modification with polydopamine and polyurethane is improved, and it can be used in alkaline solution for a long time.
[0144] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a hydrophilic polyphenylene sulfide network, characterized in that: The following steps are involved: Step 1: Weigh dopamine hydrochloride, and add it to the tris(hydroxymethyl)aminomethane solution to obtain a dopamine hydrochloride solution; The polyphenylene sulfide network was alternately cleaned with ethanol and deionized water, and after drying, it was placed in a dopamine hydrochloride solution, sodium hydroxide was added to adjust the pH value to 8.5-9, the temperature was raised to 60-70°C for reaction for 20-24 hours, and the polyphenylene sulfide network was taken out to obtain a polydopamine-modified polyphenylene sulfide network; Step 2: S21: 3-hydroxy-2-methylpropene, triphenylmethane triisocyanate, and catalyst dibutyltin dilaurate are dispersed in ethyl acetate, heated to 70-80°C under nitrogen environment, stirred for reaction for 8-10 hours, and ethyl acetate is removed by vacuum distillation to obtain a double-bond modified polyurethane prepolymer; the molar ratio of 3-hydroxy-2-methylpropene to triphenylmethane triisocyanate is (1-2):1; S22: Take toluene diisocyanate, polypropylene glycol 2000, catalyst dibutyltin dilaurate, dimethylolpropionic acid, 1,4-butanediol, raise the temperature to 80-90° C., react for 3-5 hours, and obtain a polyurethane prepolymer; S23: adding the double bond modified polyurethane prepolymer to the polyurethane prepolymer to obtain a mixed polyurethane prepolymer; S24: reacting the mixed polyurethane prepolymer and triethylamine at 50-60°C for 30-60 minutes; continuing to add ethylenediamine for 1-2 hours, and adding deionized water for emulsification for 1-2 hours to obtain a polyurethane coating with a solid content of 30-50%; S25: The polyurethane coating, 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid and a photoinitiator are mixed and stirred to obtain a binder; Step 3: The adhesive is sprayed on both sides of the polydopamine-modified polyphenylene sulfide net, with a single-side spraying thickness of 50-200 μm, and the hydrophilic polyphenylene sulfide net is obtained by ultraviolet light curing.
2. The process for preparing a hydrophilic polyphenylene sulfide network according to claim 1, characterized in that: In step 1, the mass concentration of the dopamine hydrochloride solution is 2-3%.
3. The process for preparing a hydrophilic polyphenylene sulfide network according to claim 1, characterized in that: In S22, the amount of each component, by weight, is 75-82 parts of toluene diisocyanate, 95-103 parts of polypropylene glycol 2000, 0.1-0.3 parts of catalyst dibutyltin dilaurate, 16-18 parts of dihydroxymethylpropionic acid, and 5-8 parts of 1,4-butanediol.
4. The process for preparing a hydrophilic polyphenylene sulfide network according to claim 1, characterized in that: In S23, the content of each component in the mixed polyurethane prepolymer is, by weight percentage, 30-40% of double bond modified polyurethane prepolymer and 60-70% of polyurethane prepolymer.
5. The process for preparing a hydrophilic polyphenylene sulfide network according to claim 1, characterized in that: In S24, the mass ratio of the mixed polyurethane prepolymer, triethylamine and ethylenediamine is (36~45):(5~6):(2~4).
6. The process for preparing a hydrophilic polyphenylene sulfide network according to claim 1, characterized in that: In S25, the contents of each component, by weight, are 40-50 parts of polyurethane coating, 5-15 parts of 2-acrylamide-2-methylpropane sulfonic acid, 8-10 parts of acrylic acid, and 0.8-1 parts of photoinitiator.
7. A hydrophilic polyphenylene sulfide network prepared according to the process for preparing a hydrophilic polyphenylene sulfide network according to any one of claims 1 to 6.
8. The use of the hydrophilic polyphenylene sulfide network in an alkaline water electrolysis composite diaphragm according to claim 7, characterized in that: The hydrophilic polyphenylene sulfide network is used as the supporting network, and polysulfone casting liquid is used to cast membranes on both sides to form a composite diaphragm.
9. The use according to claim 8, characterized in that: The content of each component in the polysulfone casting solution is, by weight percentage, 10-15% polysulfone resin, 75-80% zirconium dioxide, and 5-10% calcium carbonate.
Citation Information
Patent Citations
Heat-resistant liquid-absorbing diaphragm for lithium ion battery and preparation method
CN111192998A
Novel multilayer alkaline water electrolysis hydrogen production diaphragm as well as preparation method and application thereof
CN117026298A